Development and evaluation of a single-tube nested PCR with colorimetric assay for Mycobacterium tuberculosis detection - Marcela Pereira Salazar; Juliana Figueiredo da Costa Lima Suassuna Monteiro; Wlisses Henrique Veloso Carvalho-Silva; George Tadeu Nunes Diniz; Roberto Pereira Werkhauser; Lílian Maria Lapa Montenegro; Haiana Charifker Schindler (BioTechniques)
Molecular techniques have revolutionized tuberculosis (TB) diagnosis by offering a faster and more sensitive approach, detecting Mycobacterium tuberculosis (Mtb) DNA directly from samples. Single-tube nested PCR (STNPCR) combines two PCR reactions with separate oligonucleotide sets in a single tube. Moreover, colorimetric methods in PCR products have been studied for pathogen detection. Thus, this study aimed to establish a novel system based on colorimetric STNPCR for Mtb detection using microtiter plates with IS6110-amplified fragments. The results showed a general colorimetric STNPCR detection limit of 1 pg/μl. Its general sensitivity and specificity were 76.62 and 60.53%, respectively, with kappa index agreement of 0.166.